Frustration analysis of coronaviruses E protein variants in pentameric conformation - Koh, Hui Fen (Nanyang Technological University, 2023)
COVID-19 pandemic has spurred significant interest in studying coronavirus (CoV) protein design, infection process, and novel therapeutic targets. E protein is vital in coronavirus production and assembly and can potentially be a drug target through its ability to oligomerize and generate a pentameric ion channel (IC) in SARS-CoV-2. However, it is unclear if all Coronaviridae E protein homologs have this structural feature. Moreover, a recent hypothesis suggests that E protein may drive membrane remodeling through amyloid formation at the C-terminus. Thus, comparative analysis of E protein sequences from different CoV genera in this study aims to determine whether E protein across CoVs form a pentameric IC and identify critical amino acids in E protein’s transmembrane domain for oligomerization and IC formation may shed some light on these competing views. The stability analysis of representative sequences from each genus using Frustratometer Server suggests that Beta genus is the most stable in a pentameric conformation, followed by Alpha, Gamma and Delta. This finding offers new insights for future research on CoV sequence variations and structural experiments and suggests that some amino acid sequence variants from Delta genera may be incompatible with the canonical model of pentameric IC determined for SARS-CoV-2 E protein.